A Comparative Study of Deductive and Inductive Teaching of Participial Phrase: A Case Study - Jonathan Tanihardjo (Journal of English Language and Culture, 2017)
Grammar is one of the language features that are intricate for language learners. Owing to the fact that vocabulary has a substantial role in a language, many language learners are reluctant to know the rule of a language inside and out. Nonetheless, grammar is of value to avoid confusion towards the intended meaning. Gewerhr (1998) states that grammaticality is fundamental, thus the teaching of grammar should be central in a language classroom. Many teachers have been teaching grammar using various approaches, but still, errors are present in students’ performance in terms of grammatical accuracy. Thornbury (1999) suggested 2 different methods in the teaching of grammar: deductive and inductive. From years of experience in teaching grammar, the researcher has always opted for deductive method, since it is something that students are familiar with and saves time. For that reason, this study is conducted to find out which of the two methods works better. This research is focusing on the students’ ability to understand the specific topic, namely Participial Phrase. The participants of the research are 12 students of 4PBI1 and 11 students of 4PBI2, making 23 students in total. To find out the students’ knowledge and understanding, pre- and post-test were administered to both classes of 4PBI1 and 4PBI2. The results shown were really surprising, since the method widely and commonly adopted in the teaching of grammar was not good enough. Instead, the method which shows an intended result was inductive teaching. The pre- and post-test using such method was significantly different. Keywords: inductive teaching, deductive teaching, participial phrase